2022
DOI: 10.3390/microorganisms10061079
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Identification of Yeasts in Production of White-Brined Cheese

Abstract: The aim of this study was to reveal the sites of yeast contamination in dairy production and perform taxonomic characterization of potential yeast spoilers in cheese making. Occurrence of spoilage yeasts was followed throughout the manufacture of white-brined cheese at a Danish dairy, including the areas of milk pasteurization, curd processing, and packaging (26 sites in total). Spoilage yeasts were isolated from whey, old cheese curd, and air samples in viable counts of 1.48–6.27 log CFU/mL, 5.44 log CFU/g, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 61 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Our results show that C. intermedia grows relatively fast on lactose, and strains of this species have been isolated several times from lactose-rich niches including fermentation products like white-brined cheese 46 and cheese whey 47 . In these lactose-rich environments, survival likely necessitates a genetic makeup that can help outcompete rivaling microorganisms.…”
Section: Discussionmentioning
confidence: 74%
“…Our results show that C. intermedia grows relatively fast on lactose, and strains of this species have been isolated several times from lactose-rich niches including fermentation products like white-brined cheese 46 and cheese whey 47 . In these lactose-rich environments, survival likely necessitates a genetic makeup that can help outcompete rivaling microorganisms.…”
Section: Discussionmentioning
confidence: 74%
“…The appearance of yeasts in some acidified dairy products in high numbers may be caused by their ability to grow in low water activities (aw) and low temperatures, and ability to tolerate low pH and high salt concentrations [13]. The presence of yeasts can lead to various quality defects, especially when grown in high numbers 5-6 log CFU/g, and this can result in softening of the cheese texture, discoloration, off-flavours, and swelling of the cans [14]. The mean and minimum counts for yeasts and moulds, obtained in our study, were slightly higher than those for artisanal Turkish White Pickled cheese [15], while the maximum count was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Kluyveromyces marxianus, Saccharomyces cerevisiae and Candida intermedia were among the yeast isolated from Serro Minas, a traditional Brazilian cheese by Cardoso et al (2015). Abdelgadir et al (2001) 2012) isolated 36 different species, with the most prominent being Candida lusitania, Cryptococcus laurentii, S. cerevisiae).Candida intermedia, Kluyveromyces marxianus, and Pichia kudriavzevii were the most frequently isolated yeast species in white-brined cheese and have been characterized as typical dairy spoilers at the Danish Dairy (Geronikou et al, 2022).In Chal, a fermented camel milk of Golestan province of Iran, Yam et al (2015) reported Kluyveromyces lactis and K. marxianus as being the dominant yeast. This species difference with in the various fermented milk products probably due to differences in raw material, environmental factors (temperature, humidity etc.)…”
Section: Discussionmentioning
confidence: 99%